2022
DOI: 10.7150/jca.75510
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis Reveals Overexpression of both Integral Membrane and Cytosolic Tight Junction Genes in Endometrial Cancer Cell Lines

Abstract: Deregulation of tight junction (TJ) proteins and the associated disruption of TJ function has been demonstrated to play a role in the development of endometrial cancer. In the current study, we have shown overexpression of claudin-3 and -4 mRNA (by RT-PCR) and protein (by immunoblotting) in a panel of 9 human endometrial cancer cell lines. To further expand our understanding of the complex role of TJ deregulation in endometrial cancer, we also investigated the expression of 84 TJ and TJ-associated genes (encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The results showed that HR-DDR is most frequently mutated in EC, providing an avenue to explore the role of HR-DDR deficiency targeted therapy in EC [ 48 ]. In addition, the tight junction pathway, base excision repair pathway, and oocyte meiosis pathway have been shown to be involved in the occurrence and development of EC, which is consistent with our findings [ 49–51 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that HR-DDR is most frequently mutated in EC, providing an avenue to explore the role of HR-DDR deficiency targeted therapy in EC [ 48 ]. In addition, the tight junction pathway, base excision repair pathway, and oocyte meiosis pathway have been shown to be involved in the occurrence and development of EC, which is consistent with our findings [ 49–51 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, decreased ZO-3 was found in the tumor group, suggesting that tight junction damaged by downregulation of ZO-3 might promote the cancer metastasis. However, in some other studies, upregulated ZO-3 was reported to promote cancer [ 35 , 36 ]. Future studies are needed to investigate the exact role ZO-3 played in cancer.…”
Section: Discussionmentioning
confidence: 99%